A review on the use of Synthetic Aperture Radar (SAR) for monitoring shorelines and intertidal areas - Ma Carmen Millán; Erica Pellón; Erwin W.J. Bergsma; Edward Salameh; Salman Saeed Khan; Eduard Angelats; Yongjing Mao; Imen Turki; Salvatore Savastano; Sophie Mann; Andrés Payo; Nina Furcic; et al. (Coastal Engineering, 2027)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Record Rainfall from the Enhanced Southwest Monsoon in Metro Manila, Philippines: A Comparative Study of Recent Events - Lyndon Mark Payanay Olaguera; Alwin Andriel L. Bathan; Edward Kyle Badua; Erica N. Bañares; Clint Eldrick R. Petilla; John A. Manalo; Faye Abigail T. Cruz; Jose Ramon T. Villarin (Asia-Pacific Journal of Atmospheric Sciences, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Congener Conflict: Invasive Barred Owl Landscape Use Across the Range of the Northern Spotted Owl - Julianna M. A. Jenkins; Natalie M. Rugg; Raymond J. Davis; Scott A. Gremel; Aaron Henderson; Edward Henson; Mark Higley; Holly D. Horan; Christopher McCafferty; Thomas Munger; David Press; Suzanne Reffler; et al. (Journal of Biogeography, 2025)
Aim To map the probability of landscape use of invading barred owls ( Strix varia ) across the range of the threatened northern spotted owl ( S. Occidentallis Caurina ) in the Pacific Northwest, USA , identifying environmental drivers of barred owl landscape use to inform targeted management interventions. Location Forests of the Pacific Northwest, USA. Taxon Barred Owl ( Strix varia ). Methods We deployed 4081 autonomous recording units ( ARUs ) within 1027 randomly selected long‐term monitoring sites consisting of 5‐km 2 hexagons in 2023. We processed audio recordings using convolutional neural networks to detect vocalisations. We applied single‐season occupancy models at both ARU station and hexagon scales to estimate barred owl landscape use and assess associations with environmental variables. Using top models, we mapped barred owl landscape use across the full US range of the northern spotted owl, an umbrella species for conservation of the pacific northwest old‐growth forest community. Results Barred owls were widely detected, with naïve occupancy at 86.8% at the 5‐km 2 hexagon scale. We observed regional variation, with the highest landscape use in the Oregon Coast region and lower landscape use in California regions and the Washington Eastern Cascades. Landscape use was positively associated with mature forest characteristics at both broad and fine scales and negatively associated with elevation and climatic water deficit. Cumulative detection probability exceeded 90% after 2 weeks at the hexagon scale and 4 weeks at the station scale, providing guidance for future barred owl monitoring efforts. Main Conclusions Our study reveals extensive, but not ubiquitous, barred owl distribution across the range of the northern spotted owl. The findings offer a decision‐support framework for prioritising targeted management actions, particularly in regions with lower rates of barred owl landscape use. The integration of passive acoustic monitoring and AI‐based detection demonstrates a scalable approach for invasive species monitoring and conservation planning to meet management objectives in dynamic forest landscapes.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Multisite evaluation of microtensiometer and osmotic cell stem water potential sensors in almond orchards - Isaya Kisekka; Srinivasa Rao Peddinti; Peter Savchik; Liyuan Yang; Mae Culumber; Khalid Bali; Luke Milliron; Erica Edwards; Mallika Nocco; Clarissa A. Reyes; Robert J. Mahoney; Kenneth Shackel; et al. (Computers and Electronics in Agriculture, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Host and geography impact virus diversity in New Zealand’s longfin and shortfin eels - Stephanie J. Waller; Eimear Egan; Shannan Crow; Anthony Charsley; P. Mark Lokman; Erica K. Williams; Edward C. Holmes; Jemma L. Geoghegan (Archives of Virology, 2024)
The fishing and aquaculture industry is vital for global food security, yet viral diseases can result in mass fish die-off events. Determining the viromes of traditionally understudied species, such as fish, enhances our understanding of the global virosphere and the factors that influence virome composition and disease emergence. Very little is known about the viruses present in New Zealand’s native fish species, including the shortfin eel ( Anguilla australis ) and the longfin eel ( Anguilla dieffenbachii ), both of which are fished culturally by Māori (the indigenous population of New Zealand) and commercially. Through a total RNA metatranscriptomic analysis of longfin and shortfin eels across three different geographic locations in the South Island of New Zealand, we aimed to determine whether viruses had jumped between the two eel species and whether eel virome composition was impacted by life stage, species, and geographic location. We identified nine viral species spanning eight different families, thereby enhancing our understanding of eel virus diversity in New Zealand and the host range of these viral families. Viruses of the family Flaviviridae (genus Hepacivirus ) were widespread and found in both longfin and shortfin eels, indicative of cross-species transmission or virus-host co-divergence. Notably, both host specificity and geographic location appeared to influence eel virome composition, highlighting the complex interaction between viruses, hosts, and their ecosystems. This study broadens our understanding of viromes in aquatic hosts and highlights the importance of gaining baseline knowledge of fish viral abundance and diversity, particularly in aquatic species that are facing population declines.

Planktonic habitats in the Amazon Plume region of the Western Tropical North Atlantic - Anh H. Pham; Noémie Choisnard; Ana Fernández-Carrera; Ajit Subramaniam; Erica K. Strope; Edward J. Carpenter; Maren Voss; Joseph P. Montoya (Frontiers in Marine Science, 2024)
The Western Tropical North Atlantic is a highly dynamic marine system where the Amazon River Plume (ARP) generates a patchwork of environmental conditions that favor different phytoplankton groups. To study phytoplanktonic community structure in such heterogeneous conditions, we used a set of five standard ship-based measurements taken from oceanographic surveys between 2010 and 2021 to characterize different habitat types. We then utilized a variety of multiparametric approaches to examine phytoplankton biodiversity in the different habitats to assess the biological relevance of our delineated habitats. Our approach generated a consistent set of habitat types across cruises carried out in multiple different years and the Amazon’s two predominant (wet and dry) seasons. Our phytoplankton community analyses revealed strong distinctions among all habitats along the plume gradient using in-vivo fluorescence and diagnostic pigments, and clear contrasts of diazotroph community along the mesohaline waters using direct cell-count, a pattern consistent with niche partitioning among similar species. The few apparent mismatches we found between phytoplankton community composition and habitat may reflect recent hydrographic changes driven by mixing and/or upwelling and thus may be a useful index to biologically-relevant temporal variation. Our habitat classification approach is straightforward and broadly applicable in identifying biologically distinct areas within heterogeneous and dynamic regions of the ocean.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The National Conference on Health Disparities Student Research Forum - Marvella E. Ford; Angela M. Malek; Erica Martino; Latecia Abraham-Hilaire; Oluwole Ariyo; Dana Burshell; Gloria Callwood; Laura Campbell; Kimberly Cannady; Courtney Chavis; Brittney Crawford; Andie Edwards; et al. (Journal of Cancer Education, 2023)
The annual National Conference on Health Disparities (NCHD) was launched in 2000. It unites health professionals, researchers, community leaders, and government officials, and is a catalyzing force in developing policies, research interventions, and programs that address prevention, social determinants, health disparities, and health equity. The NCHD Student Research Forum (SRF) was established in 2011 at the Medical University of South Carolina to build high-quality biomedical research presentation capacity in primarily underrepresented undergraduate and graduate/professional students. This paper describes the unique research training and professional development aspects of the NCHD SRF. These include guidance in abstract development, a webinar on presentation techniques and methods, a vibrant student-centric conference, and professional development workshops on finding a mentor and locating scholarship/fellowship funding, networking, and strategies for handling ethical issues in research with mentors. Between 2011 and 2018, 400 undergraduate and graduate/professional students participated in the NCHD SRF. Most students were women (80.5%). Approximately half were African American or black (52.3%), 18.0% were white, and 21.3% were of Hispanic/Latinx ethnicity. The NCHD SRF is unique in several ways. First, it provides detailed instructions on developing a scientific abstract, including content area examples. Second, it establishes a mandatory pre-conference training webinar demonstrating how to prepare a scientific poster. Third, it works with the research mentors, faculty advisors, department chairs, and deans to help identify potential sources of travel funding for students with accepted abstracts. These features make the NCHD SRF different from many other conferences focused on students’ scientific presentations.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Cryptococcus gattii VGII isolated from native forest and river in Northern Brazil - Amaury dos Santos Bentes; Bodo Wanke; Márcia dos Santos Lazéra; Ana Karla Lima Freire; Roberto Moreira da Silva Júnior; Diego Fernando Silva Rocha; Silviane Bezerra Pinheiro; Steven Edward Zelski; Ani Beatriz Jackisch Matsuura; Liliane Coelho da Rocha; Erica Simplício de Souza; João Vicente Braga de Souza (Brazilian Journal of Microbiology, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Targeted transgene integration in plant cells using designed zinc finger nucleases - Charles Q. Cai; Yannick Doyon; W. Michael Ainley; Jeffrey C. Miller; Russell C. DeKelver; Erica A. Moehle; Jeremy M. Rock; Ya-Li Lee; Robbi Garrison; Lisa Schulenberg; Ryan Blue; Andrew Worden; et al. (Plant Molecular Biology, 2009)

TLR5 and Ipaf: dual sensors of bacterial flagellin in the innate immune system - Edward A. Miao; Erica Andersen-Nissen; Sarah E. Warren; Alan Aderem (Seminars in Immunopathology, 2007)

Osteoblast Elastic Modulus Measured by Atomic Force Microscopy Is Substrate Dependent - Erica Takai; Kevin D. Costa; Aisha Shaheen; Clark T. Hung; X. Edward Guo (Annals of Biomedical Engineering, 2005)

Microsatellite Markers for the Paddlefish (Polyodon spathula) - Edward J. Heist; Erica H. Nicholson; Justin T. Sipiorski; Devon B. Keeney (Conservation Genetics, 2002)

Differential effects of tropical arbuscular mycorrhizal fungal inocula on root colonization and tree seedling growth: implications for tropical forest diversity - Erica T. Kiers; Catherine E. Lovelock; Eileen L. Krueger; Edward A. Herre (Ecology Letters, 2000)
The potential for mycorrhizae to influence the diversity and structuring of plant communities depends on whether their affinities and effects differ across a suite of potential host species. In order to assess this potential for a tropical forest community in Panama, we conducted three reciprocal inoculation experiments using seedlings from six native tree species. Seeds were germinated in sterile soil and then exposed to arbuscular mycorrhizal fungi in current association with naturally infected roots from adults of either the same or different species growing in intact forest. The tree species represent a range of life histories, including early successional pioneers, a persistent understory species, and emergent species, typical of mature forest. Collectively, these experiments show: (i) the seedlings of small‐seeded pioneer species were more dependent on mycorrhizal inocula for initial survival and growth; (ii) although mycorrhizal fungi from all inocula were able to colonize the roots of all host species, the inoculum potential (the infectivity of an inoculum of a given concentration) and root colonization varied depending on the identity of the host seedling and the source of the inoculum; and (iii) different mycorrhizal fungal inocula also produced differences in growth depending on the host species. These differences indicate that host–mycorrhizal fungal interactions in tropical forests are characterized by greater complexity than has previously been demonstrated, and suggest that tropical mycorrhizal fungal communities have the potential to differentially influence seedling recruitment among host species and thereby affect community composition.

Immunoreactivity for the Fas ligand in the mammalian enteric nervous system - Edward J. Parr; Erica B. Myles; Menachem Hanani; Dan Seror; Karl T. Riabowol; Keith A. Sharkey (Cell and Tissue Research, 1997)